Mesenchymal Stromal Cells: Role in the BM Niche and in the Support of Hematopoietic Stem Cell Transplantation - Stefania Crippa; Maria Ester Bernardo (HemaSphere, 2018)
Abstract. Mesenchymal stromal cells (MSCs) are key elements in the bone marrow (BM) niche where they interact with hematopoietic stem progenitor cells (HSPCs) by offering physical support and secreting soluble factors, which control HSPC maintenance and fate. Although necessary for their maintenance, MSCs are a rare population in the BM, they are plastic adherent and can be ex vivo expanded to reach numbers adequate for clinical use. In light of HSPC supportive properties, MSCs have been employed in phase I/II clinical trials of hematopoietic stem cell transplantation (HSCT) to facilitate engraftment of hematopoietic stem cells (HSCs). Moreover, they have been utilized to expand ex vivo HSCs before clinical use. The available clinical evidence from these trials indicate that MSC administration is safe, as no acute and long-term adverse events have been registered in treated patients, and may be efficacious in promoting hematopoietic engraftment after HSCT. In this review, we critically discuss the role of MSCs as component of the BM niche, as recent advances in defining different mesenchymal populations in the BM have considerably increased our understanding of this complex environment. Moreover, we will revise published literature on the use of MSCs to support HSC engraftment and expansion, as well as consider potential new MSC application in the clinical context of ex vivo gene therapy with autologous HSC.